2023
DOI: 10.1038/s41598-023-30305-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor 1 is not a major causative factor for exacerbation in a mouse model of SARS-CoV-2 infection

Abstract: Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains a global pandemic. Although several vaccines targeting SARS-CoV-2 spike proteins protect against COVID-19 infection, mutations affecting virus transmissibility and immune evasion potential have reduced their efficacy, leading to the need for a more efficient strategy. Available clinical evidence regarding COVID-19 suggests that endothelial dysfunction with thrombosis is a central pathogenesis of progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Further, lack of PAI-1 was particularly deleterious in aged mice, but had little effect on young mice highlighting the importance of age as a biological variable in studies with rodents. Most prior studies reporting a deleterious role for PAI-1 were conducted on young mice using a non-infectious endotoxemia model ( Murakami et al, 1997 ; Gupta et al, 2015 ; Nakayama et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, lack of PAI-1 was particularly deleterious in aged mice, but had little effect on young mice highlighting the importance of age as a biological variable in studies with rodents. Most prior studies reporting a deleterious role for PAI-1 were conducted on young mice using a non-infectious endotoxemia model ( Murakami et al, 1997 ; Gupta et al, 2015 ; Nakayama et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work emphasizing a deleterious role for PAI-1 in AKI showed that young mice lacking PAI-1 have increased survival, improved kidney function, decreased apoptosis, reduced inflammation, attenuated fibrin deposition in the kidneys, and increased levels of circulating activated protein C as compared to WT mice after LPS challenge ( Gupta et al, 2015 ; Nakayama et al, 2023 ). These benefits were similarly observed in a mutant mouse model where the interaction between PAI-1 and vitronectin was abolished, verifying a key role for this interaction in mediating PAI-1’s effects on the kidney ( Gupta et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations